1999
DOI: 10.1002/j.1556-6676.1999.tb02453.x
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Effects of Incest on Parenting: Skills, Abilities, and Attitudes

Abstract: Women's perceptions of generational influences of incest on their skills, abilities, and attitudes toward parenting their own children were investigated. Overarching themes that emerged were classified as unbalanced development, disconnected lives, and disowned dramas. Implications for clinical intervention, parent training, and future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The quantitative work in this area has suggested that when compared to their non-abused counterparts, mothers who are also survivors of CSA have greater difficulty with parenting practices including maintaining appropriate boundaries with children (DiLillo, 2001), being too permissive, and engaging in harsh discipline (DiLillo & Damashek, 2003). Only a few qualitative studies have addressed the impact of CSA on women’s parenting (Armsworth & Stronck, 1999; Burkett, 1991; Roller, 2011; Wright, Fopma-Loy, & Oberle, 2012) even though both quantitative and qualitative studies have been recommended in advancing the study of violence against women (Testa, Livingston, & VanZile-Tamsen, 2011). …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The quantitative work in this area has suggested that when compared to their non-abused counterparts, mothers who are also survivors of CSA have greater difficulty with parenting practices including maintaining appropriate boundaries with children (DiLillo, 2001), being too permissive, and engaging in harsh discipline (DiLillo & Damashek, 2003). Only a few qualitative studies have addressed the impact of CSA on women’s parenting (Armsworth & Stronck, 1999; Burkett, 1991; Roller, 2011; Wright, Fopma-Loy, & Oberle, 2012) even though both quantitative and qualitative studies have been recommended in advancing the study of violence against women (Testa, Livingston, & VanZile-Tamsen, 2011). …”
mentioning
confidence: 99%
“…We are aware of only four qualitative studies examining the impact of CSA on parenting (Armsworth & Stronck, 1999; Burkett, 1991; Roller, 2011; Wright et al, 2012). Burkette (1991) conducted a study of twenty mothers with histories of CSA committed by a family member and twenty women without such abuse histories.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Groups are beneficial to survivors in a number of ways. First, groups serve as a support system and help members develop a sense of belonging, thereby reducing their sense of isolation (Armsworth & Stronck, 1999;Draucker, 1999;Zaidi, 1999) and instilling a sense of hope (Gorey et al, 2001). Developing relationships within the group reduces the mistrust of others that survivors often experience, and this opportunity helps them begin to form more meaningful relationships with others (Ainscough & Toon, 1993;Draucker, 1999;Lubin et al, 1998).…”
Section: Choate Henson / Adult Survivors 107mentioning
confidence: 97%